Understanding the knowledge and experience of menarche among secondary school female students in Nnewi, Anambra State, Nigeria - Chiekezie, Chinonuju Franklin; Edeh, Gabriel Chidera; Ekwebene, Onyeka Chukwudalu; Chiekezie, Chisimdi Marysandra; Chiekezie, Chukwuebuka Kingsley; Okonkwo, Benjamin Chukwunonso; Ashibogwu, Ezinneamaka Maureen; Awugosi, Michael Chukwuebuka (International Journal of Research in Medical Sciences, 2024)
Background: Menstruation, a key physiological change in females of reproductive age, necessitates providing young girls with crucial information on menarche to better prepare them. Methods: This study assessed the knowledge and experience of menarche among secondary school female students in Nnewi, Anambra State, Nigeria, utilizing a descriptive cross-sectional survey method. Conducted from August to September 2023, the study involved 420 participants and employed multistage sampling for selection. Results: The findings revealed a paradoxical decrease in the mean age of menarche to 12.02 +/- 1.15 years, with most girls experiencing menarche at age 13. Notably, 91.4% of participants had substantial knowledge of menarche, primarily acquired from mothers. Although 86.9% recognized menarche as a normal puberty change, experiences varied: 45.5% felt normal, 39.3% were afraid, and 12.9% felt ashamed during their menarche. Conclusions: The study concludes that despite high awareness levels, poor menarche experiences prevail due to inadequate preparation. It recommends enhanced awareness campaigns in schools, spearheaded by NGOs and health workers, to educate and prepare young girls for menarche effectively.